Le unità fraseologiche: uno studio nell’apprendimento dell’italiano l2 (PHRASIS | Rivista di studi fraseologici e paremiologici, 2022)
The contribution analyzes the Phraseological Units (PU) in Italian and their learning by non-natives. For the study, reference is made to various studies including the CEFR, which provides some explicit or implicit indications for teaching them at different competence levels. In order to observe their use, a sample of written productions was collected at the end of a B2 level course. The research question aims to suggest a more systematic treatment of PU emerging in learners’ interlanguages. The study shows that the acquisition of PU, different among informants and PU, would make desirable a more calibrated approach in teaching them, useful for teachers and textbooks authors.
Keywords: phrasal units, acquisition, teaching, phrasal competence